Clinical characteristics of gynecologic cancer patients who respond to salvage treatment with Lingzhi - Prapaporn Suprasert (2018)
Lingzhi or Ganoderma lucidum is a popular medicinal mushroom used as a health promotion herb in China and other Asian countries for thousands of years. There have many previous studies about the anti-cancer effects of lingzhi especially in vitro. The present study reports the clinical data of 5 gynecologic cancer patients who achieved stability in the disease after ingestion of lingzhi in the form of fruit body water extract and spores in a salvage setting. This report has been written to enhance the data describing the effect of lingzhi in cancer patients.